Deforestation awareness among the community living near mangroves in Mukim Tanjung Kupang, Johor, Malaysia - N. S., Sarmin; Ismail, Mohd Hasmadi; H. Z., Pakhriazad; Awang, Khairil Wahidin; Mohamad Kasim, Mohamad Roslan (Publications International, 2017)
A study was carried out on the deforestation awareness among the community living nearest to Sungai Pulai mangrove forest under mukim (sub-district) Tanjung Kupang in Johor Bahru, Peninsular Malaysia. A Structured questionnaire was used to collect data on respondents’ socioeconomic condition, their familiarity to mangroves and awareness from six villages which have been selected randomly. Majority of the respondents were male, Malay, Muslim and from middle aged group. About 82% respondents had some level of education. Average household size was 5.5. About 71% respondents’ livelihoods were dependent on mangrove ecosystem of which 65% were fishermen, 5% aquaculture and 1% tourism. Mean monthly income of respondents was quite lower than national average income. Moreover, monthly average income of mangrove dependent group was lower than the non mangrove dependent group. About 93% of the respondents were somehow familiar to mangroves. Responden ts mean awareness score of 3.78 indicates respondents were aware about the mangroves. It was also found that male had significantly higher awareness than female for two out of ten awareness components. Likewise,mangrove dependent group had significantly higher awareness than the non- mangrove dependent group for six out of ten awareness components.